Pelvic floor dysfunction and electrophysiology in postpartum women at 6–8 weeks - Wu, Jia-Cong; Yu, Xiao-Li; Ji, Hui-Jing; Lou, Hai-Qin; Gao, Hong-Ju; Huang, Guo-Qin; Zhu, Xiao-Li (Frontiers in Physiology, 2023)
Objective: To investigate the incidence of pelvic floor dysfunction (PFD) and electrophysiological indicators in postpartum women at 6–8 weeks and explore the influence of demographic characteristics and obstetric factors. Methods: A survey questionnaire collected information about the conditions of women during their pregnancy and puerperal period and their demographic characteristics; pelvic organ prolapse quantitation (POP-Q) and pelvic floor muscle electrophysiology (EP) examination were conducted in postpartum women at 6–8 weeks. Results: Vaginal delivery was a risk factor for anterior pelvic organ prolapse (POP) (OR 7.850, 95% confidence interval (CI) 5.804–10.617), posterior POP (OR 5.990, 95% CI 3.953–9.077), anterior and posterior stage II POP (OR 6.636, 95% CI 3.662–15.919), and postpartum urinary incontinence (UI) (OR 6.046, 95% CI 3.894–9.387); parity was a risk factor for anterior POP (OR 1.397,95% CI 0.889–2.198) and anterior and posterior stage II POP (OR 4.162, 95% CI 2.125–8.152); age was a risk factor for anterior POP (OR 1.056, 95% CI 1.007–1.108) and postpartum UI (OR 1.066, 95% CI 1.014–1.120); body mass index (BMI) was a risk factor for postpartum UI (OR 1.117, 95% CI 1.060–1.177); fetal birth weight was a risk factor for posterior POP (OR 1.465, 95% CI 1.041–2.062); and the frequency of pregnancy loss was a risk factor for apical POP (OR 1.853, 95% CI 1.060–3.237). Conclusion: Pelvic floor muscle EP is a sensitive index of early pelvic floor injury. The changes in muscle strength and fatigue degree coexist in different types of postpartum PFD, and each has its own characteristics.